Historia de la salud mental en Ecuador y el rol de la Universidad Central del Ecuador, viejos paradigmas en una sociedad digitalizada - Zúñiga Carrasco, Danny Raúl (2018)
Context: mental health in Ecuador has its origins where the magic-religious conception directed the understanding and treatment of the evils of the spiritDiscussion and analysis: during the colony, with the implementation of the European paradigm, the assistance of the so-called mental patients was based on charity and psychiatry, was used to separate the "undesirables" from the rest of society. During the republic era, great characters emerged that contributed tothe implementation of the bases of what would later be mental health and its components.Conclusion: from the public institution and the academy, it has not been possible to reconcile criteria. Current public policies are isolated and unsustainable with the stigma and biologist's approach